Strategies to Construct a Chemical‐Fuel‐Driven Self‐Assembly. Issue 4 (11th February 2020) - Wang, Guangtong; Liu, Shaoqin
Abstract: Fuel‐driven self‐assembly widely exists in the biological world since functional micro‐ or nanostructures in living bodies are usually transiently formed by biomolecular self‐assembly far from thermodynamic equilibrium driven by active molecules (chemical fuel), for example, adenosine triphosphate (ATP). Therefore, research focusing on artificial fuel‐driven self‐assembly has drawn extensive attention in recent years. Compared with spontaneous molecular self‐assembly at thermodynamic equilibrium, constructing a fuel‐driven self‐assembly remains complicated because it requires a delicately designed chemical reaction network mainly involving an "activation" and a "deactivation". In this Minireview, we will review recent developments in fuel‐driven self‐assembly and generalize several strategies for constructing such a self‐assembly. Besides that, the functional micro‐ or nanostructures and materials achieved by these fuel‐driven self‐assemblies will also be discussed. Abstract : Ingenious design : Strategies to construct fuel‐driven self‐assembled systems are reviewed, including systems in which the construction is assisted by enzymes, as well as those employing entirely synthetic chemicals. Applications, challenges and future perspectives of fuel‐driven self‐assembly are discussed.